IDDF2018-ABS-0188 Effect of nursing intervention on acetic acid chromoendoscopy for determining chronic atrophic gastritis. (June 2018) - Tan, Wenhui; Wu, Jiachuan; Wang, Fang; Ye, Lifang; Lv, Fang; He, Ling; Kang, Qian
Abstract : Background: To investigate the effect of the nursing intervention on acetic acid chromoendoscopy (AAC) for determining chronic atrophic gastritis. Methods: 60 patients with chronic atrophic gastritis were enrolled in our study from January 2016 to August 2017. Patients were randomly divided into AAC group (n=30) and non-AAC group (n=30). After endoscopic management and nursing intervention, SAS and SDS scores, clinical characteristics, individual tolerance and endoscopic diagnosis were collected and analysed both groups. Results: No statistical significance between ACC group and non-ACC group in SAS and SDS scores, clinical characteristics and individual tolerance (p>0.05). DBP, SBP and pulse were much lower in ACC group than non-ACC group ((p>0.05)). The accuracy, sensitivity and specificity were 91.33%, 76.82% and 97.38% respectively in the ACC group, while they were 86.24%, 75.26% and 95.41% in the non-ACC group. Conclusions: Acetic acid chromoendoscopy is valuable for the diagnosis of chronic atrophic gastritis. And nursing intervention could safely and vastly improve SAS and SDS scores, DBP, SBP and pulse, even the tolerance during gastroscopy.